BREAD QUALITY SUBSTITUTED BY POTATO STARCH INSTEAD OF WHEAT FLOUR - F. Nemar; A. Dilmi Bouras; M. Koiche; N-E. Assal; A. Mezaini; J. Prodhomme (Chiriotti Editori, 2015)
Wheat bread constitutes the most regularly consumed food in the World, the international market for wheat undergoes strong pressure and prices are unceasingly increasing. The aim of this study is to substitute wheat flour by potato starch in bread preparation. Mixtures flours were characterized for composition, damaged starch, and Alveograph properties. According to the results of alveograph parameters, they decrease with the rate of incorporation of potato starch. This decrease can be corrected by adding vital gluten. The results of physicochemical analysis showed a decrease in protein levels, an increase in moisture content (about 2%) and carbohydrates levels due to the composition of potato starch. However, sensory analysis (p ≤ 0.05) showed that the addition 80% of potato starch leads to bread with better characteristics: taste, colour and odour, based on that, it is highly advisable as an ingredient in the standard preparation of wheat bread.